HUBUNGAN PENGETAHUAN DAN SIKAP TENTANG KANKER PAYUDARA DENGAN TINDAKAN SADARI PADA WANITA USIA SUBUR DI KECAMATAN LAWE BULAN KEBUPATEN ACEH TENGGARA TAHUN 2021 - Purnama Sari Cane; Joharsah Joharsah; Fika Lestari (Jurnal Maternitas Kebidanan, 2021)
Breast cancer is a malignancy that comes from glandular cells, glandular channels and tissues of the breast glands. This is because women of childbearing age do not understand the importance of conscious action in early detection and the absence of early socialization in the environment. The purpose of this study is to find out the relationship of knowledge and attitudes about breast cancer with conscious actions in women of childbearing age in Lawe Bulan District of Southeast Aceh Regency. This research uses analytical survey research methods with cross sectional research designs. The population is all women of childbearing age in Lawe Bulan District of Southeast Aceh Regency. Sampling technique is taken simply random sampling with a sample number of 110 respondents. The study used primary data and secondary data and chi square tests were conducted. The results showed that there is a strong link between knowledge and attitudes about breast cancer and the act of being aware of breast cancer